From support to therapy: rethinking the role of nutrition in acute graft-versus-host disease - Limpert, Rachel; Pan, Pan; Wang, Li-Shu; Chen, Xiao (Frontiers in Immunology, 2023)
Allogeneic Hematopoietic stem cell transplantation (HSCT) offers a potential cure for patients with hematologic malignancies. Unfortunately, graft-versus-host disease (GVHD) remains a major obstacle to the greater success of this treatment. Despite intensive research efforts over the past several decades, GVHD is still a major cause of morbidity and mortality in patients receiving allogeneic HSCT. The genetic disparity between donor and recipient is the primary factor that dictates the extent of alloimmune response and the severity of acute GVHD. However, some nongenetic factors are also actively involved in GVHD pathogenesis. Thus, identifying host factors that can be readily modified to reduce GVHD risk is of important clinical significance. We are particularly interested in the role of nutrition, as a nongenetic factor, in the etiology and management of GVHD. In this article, we summarize recent findings regarding how different routes of nutritional support and various dietary factors affect GVHD. Since diet is one of the most important factors that shape gut microbiota, we provide evidence for a potential link between certain nutrients and gut microbiota in recipients of allogeneic HSCT. We propose a shifting role of nutrition from support to therapy in GVHD by targeting gut microbiota.